(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
An analysis of influence of small business on the economy competitiveness of different countries is presented in the article. A comparison of criteria for the classification of enterprises as well as measures and programmes to support small business in Russia and other countries is performed. The analytical data reflecting the state of small business in Russia is presented.